Design Method for Contra-Rotating Propellers for High-Speed Crafts: Revising the Original Lerbs Theory in a Modern Perspective - Stefano Brizzolara; Davide Grassi; Emilio P. Tincani (International Journal of Rotating Machinery)
The main theoretical and numerical aspects of a design method for optimum contrar-rotating (CR) propellers for fast marine crafts are presented. We propose a reformulated version of a well-known design theory for contra-rotating propellers, by taking advantage of a new fully numerical algorithm for the calculation of the mutually induced velocities and introducing new features such as numerical lifting surface corrections, use of an integrated modern cavitation/strength criteria, a modified method to consider different numbers of blades among the two propellers, and to allow for an unloading function in the search for the optimal circulation distribution. The paper first introduces the main theoretical principles of the new methods and then discusses the influence of the main design parameters on an emblematic example of application in the case of counter rotating propellers for a pod propulsor designed for fast planing crafts (35 knots and above).